2019
DOI: 10.1111/head.13499
|View full text |Cite
|
Sign up to set email alerts
|

Promote Biomarker Discovery by Identifying Homogenous Primary Headache Subgroups

Abstract: Within‐ and between‐study heterogeneity impede identification of valid primary headache biomarkers. Homogenous subgroup identification and investigation of differential biochemical profiles and networks within and across headache categories, based on statistical techniques, might promote biomarker discovery. When studying common primary headaches with a multifactorial etiology, variability might be captured at different levels (eg, genetics, clinical features, comorbidities, triggers). Moreover, focus on bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…When comparing the results from 2 recently published CGRP studies with focus on migraine, contradictory results also occurred 40,46 . This has in part been discussed by Frederiksen 64 . In this SR‐MA, a tendency appeared showing that the most notable results were obtained when investigating CGRP in central blood from migraine patients in the ictal compared with the interictal headache phase.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…When comparing the results from 2 recently published CGRP studies with focus on migraine, contradictory results also occurred 40,46 . This has in part been discussed by Frederiksen 64 . In this SR‐MA, a tendency appeared showing that the most notable results were obtained when investigating CGRP in central blood from migraine patients in the ictal compared with the interictal headache phase.…”
Section: Discussionmentioning
confidence: 93%
“…Reporting a wide range of factors in future studies with focus on signaling molecules will allow us to assess different sources of confounding in future SR‐MAs which distort the exposure‐outcome association and thus, promote the biomarker discovery process (eg, the EQUATOR and SAMPL guidelines might be of use 101 ). Other ideas on how to promote primary headache biomarker discovery were discussed by Frederiksen 64 …”
Section: Discussionmentioning
confidence: 99%
“…Measuring CGRP in migraine patients has led to a better understanding of pain in migraine pathophysiology as well as it laid the foundation of the development of new abortive and prophylactic treatments ( 40 ). Further, the neuropeptide is recognized as a marker for the acute migraine attack and it might be a marker for migraine itself which could help to objectify the diagnosis in the future ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…From these studies, it can be concluded that CGRP is a marker of the migraine attack. However, due to inconsistent findings in the overall studies, standardization of study procedures is needed to draw further conclusions (67)(68)(69).…”
Section: Figure 2 |mentioning
confidence: 99%
“…Migraine is a highly prevalent and a disabling neurological disease (1) and, so far, specific biomarkers have yet not been validated, which reflects its complexity and dynamic character (24). However, the most studied molecule is the calcitonin gene related peptide (CGRP), which has a clear implication in migraine pathophysiology (5,6), underpinned by the arrival of effective therapies targeting CGRP pathways (7).…”
Section: Introductionmentioning
confidence: 99%